1978
DOI: 10.1007/bf01844019
|View full text |Cite
|
Sign up to set email alerts
|

The firstH- 2 mutant workshop

Abstract: The major accomplishment of the Workshop was probably the realization of many of its participants that most of the 21 availableH- 2 variants aretrue mutations very likely derived from single nucleotide substitutions. Any theory of the pleiotropic effect of theH- 2 genes must now take this fact into account; such theories must also consider the observation that a wide variety of immunological phenomena are affected byH- 2 mutations and thus, apparently, are controlled by a single gene.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
1

Year Published

1980
1980
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(48 citation statements)
references
References 46 publications
6
41
1
Order By: Relevance
“…Analysis of our data show that although in most cases the residual cytotoxicity exerted by the nonadherent subsets of CTL follows the presence or absence of public specificities, in two cases (Table III, C3H.OL targets) residual cytotoxicity was observed, although no public specificities should have been detected. This finding is in accordance with the fact that CTL can be developed between serologically identical H-2 mutants, suggesting that other determinants than those recognized by alloantibodies could act as targets for CTL (18). However, it has been recently suggested that antibodies could be raised between such mutants by using appropriate immunization (18).…”
Section: Adsorption Of B I Obr Anti-b L Oa Ctl On Macrophage Monolasupporting
confidence: 75%
See 1 more Smart Citation
“…Analysis of our data show that although in most cases the residual cytotoxicity exerted by the nonadherent subsets of CTL follows the presence or absence of public specificities, in two cases (Table III, C3H.OL targets) residual cytotoxicity was observed, although no public specificities should have been detected. This finding is in accordance with the fact that CTL can be developed between serologically identical H-2 mutants, suggesting that other determinants than those recognized by alloantibodies could act as targets for CTL (18). However, it has been recently suggested that antibodies could be raised between such mutants by using appropriate immunization (18).…”
Section: Adsorption Of B I Obr Anti-b L Oa Ctl On Macrophage Monolasupporting
confidence: 75%
“…This finding is in accordance with the fact that CTL can be developed between serologically identical H-2 mutants, suggesting that other determinants than those recognized by alloantibodies could act as targets for CTL (18). However, it has been recently suggested that antibodies could be raised between such mutants by using appropriate immunization (18).…”
Section: Adsorption Of B I Obr Anti-b L Oa Ctl On Macrophage Monolasupporting
confidence: 75%
“…The stud males were either B6.CH_2bml or B6/By (H-2b). The bml mutation arose in a (B6/By X BALB/c)F, hybrid and was introduced into the B6/By strain by serial backcrossing to derive the congenic B6.C-H-2bml strain (10). Thus, the only evident genetic difference between these two strains is in the H-2K gene, and the only known structural difference is in the H-2K cell-surface glycoprotein-namely, amino acid substitutions at positions 152, 155, and 156, corresponding to differences within a sequence of 13 nucleotides within H-2K (11,12).…”
mentioning
confidence: 99%
“…Singer, Bethesda, MD. The mouse strains used in this study, their H-2 haplotypes, and the structural alterations in the H-2 molecules of the mutant mouse strains are listed in Table I ( [33][34][35][36][37].…”
Section: Methodsmentioning
confidence: 99%